P112 Association of sputum Pseudomonas aeruginosa (PsA) isolation and length of hospital stay in patients with chronic obstructive pulmonary disease (COPD). (16th November 2010) - Ali, A; Bhattacharya, M; Corcoran, J; Chakraborty, B; Thomas, A; Raza, M; Mukherjee, R
Abstract : Introduction and objectives: A lot of effort and investment has been made to improve the length of stay (LOS) in COPD related admissions with variable success. It is known that numbers of hospital admissions and re-admissions have increased. Bacterial infections contribute to acute exacerbation of COPD (AECOPD) in 50% of cases; PsA is a probable pathogenic organism (PPM) causing acute or chronic infection in severe COPD patients. We set out to examine whether PsA in sputum influenced the length of stay as this PPM is not covered by the routinely used first line antibiotics. Method: A retrospective audit was carried out examining the sputum culture results and LOS in all COPD admissions in an acute hospital from 1 January 2009 to 31 December 2009, patients were identified from coding (ICD: J44). Sputum cultures were attempted (and collected in all sputum producers) by a dedicated respiratory team as a routine for all COPD admissions throughout that period, which was established as part of service improvement well before the audit. Results were obtained from Pathology department database. Patients were divided into sputum producing group and non-producers, Sputum producers were further divided into patients with positive sputum culture of PPM and non-pathogenic organisms. PsA growers were identified. Median LOS was calculated to be 5 days and all groups were compared with this duration as a standard for their LOS. Results: Total admissions with COPD were 332; 203 were sputum producers and 122 had bacterial isolates. There were 37 PsA growers. LOS was seen to be 5 or more days in: 121 sputum producers vs 47 non-producers, p=0.000046. 79 PPM culture positive patients vs 42 without bacterial growth, p=0.067; PsA growers vs. all admissions, p=0.000744, PsA vs all sputum producers p=0.0126, PsA vs all PPM, p=0.041. Conclusions: PsA infection is associated with significantly longer LOS in hospital. All COPD patients should possibly be screened for PsA infection (and possibly underlying bronchiectasis) to inform the selection of antibiotics, which is likely to reduce LOS and may reduce re-admission rates.